Comparison of an Inside Stent and a Fully Covered Self-Expandable Metallic Stent as Preoperative Biliary Drainage for Patients with Resectable Perihilar Cholangiocarcinoma - Hiroshi Mori; Hiroki Kawashima; Eizaburo Ohno; Takuya Ishikawa; Kentaro Yamao; Yasuyuki Mizutani; Tadashi Iida; Masanao Nakamura; Masatoshi Ishigami; Shunsuke Onoe; Takashi Mizuno; Tomoki Ebata; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background. There is a need for a more tolerable preoperative biliary drainage (PBD) method for perihilar cholangiocarcinoma (PHCC). In recent years, inside stents (ISs) have attracted attention as a less suffering PBD method. Few studies have compared IS with a fully covered self-expandable metallic stent (FCSEMS) as PBD for resectable PHCC. The aim of this study is to compare them. Methods. This study involved 86 consecutive patients (IS: 51; FCSEMS: 35). The recurrent biliary obstruction (RBO) rate until undergoing surgery or being diagnosed as unresectable, time to RBO, factors related to RBO, incidence of adverse events related to endoscopic retrograde cholangiography, and postoperative complications associated with each stent were evaluated retrospectively. Results. There was no significant difference between the two groups in the incidence of adverse events after stent insertion. After propensity score matching, the mean (SD) time to RBO was 37.9 (30.2) days in the IS group and 45.1 (35.1) days in the FCSEMS group, with no significant difference (P=0.912, log-rank test). A total of 7/51 patients in the IS group and 3/35 patients in the FCSEMS group developed RBO. The only risk factor for RBO was bile duct obstruction of the future excisional liver lobe(s) due to stenting (HR 29.8, P=0.008) in the FCSEMS group, but risk factors could not be indicated in the IS group. There was no significant difference in the incidence of bile leakage or liver failure. In contrast, pancreatic fistula was significantly more common in the FCSEMS group (13/23 patients) than in the IS group (3/28 patients) (P<0.001), especially in patients who did not undergo pancreatectomy (P=0.001). Conclusions. As PBD, both IS and FCSEMS achieved low RBO rates. Compared with FCSEMS, IS shows no difference in RBO rate, is associated with fewer postoperative complications, and is considered an appropriate means of PBD for resectable PHCC. This trail is registered with UMIN000025631.